Nafion Layer-Enhanced Anatase TiO2 Nanoparticles for Photosynthetic CO2 Conversion - Mokri, Nurul Afiqah; Ching, Oh Pei; Leng, Chew Thiam; Nasir, Rizwan (Springer Science and Business Media Deutschland GmbH, 2025)
In pursuing efficient photosynthetic CO2 conversion, using TiO2 as a photocatalyst has encountered challenges, including high bandgap energy levels and recombination rates of photogenerated charges. Addressing these issues, a key strategy involves modifying the anatase TiO2 surfaces with a thin coating layer, wherein the introduction of oxygen vacancies at non-lattice regions proves instrumental in retaining long-lived electrons essential for CO2 photoreduction. Notably, this study introduces a novel approach by incorporating perfluorinated Nafion with a significant distribution of sulfonyl groups at TiO2/Nafion interfaces on anatase TiO2 nanoparticles (S-TiO2) synthesized via sonothermal assisted sol-gel route. Furthermore, the Nf/S-TiO2 nanoparticles exhibit lowest electron-hole recombination, showcasing improved in photogenerated carrier transport from valence to conduction band. This research pioneers the exploration of the effect of Nafion coating on light absorption wavelength and photogenerated charge carrier activities using luminescence spectroscopy. The proposed ranking of photocatalytic activity—Nf/C-TiO2 < C-TiO2 < S-TiO2 < Nf/S-TiO2—underscores the potential of the Nafion layer in augmenting the suppression of undesired recombination of holes and electrons. Improved light utilisation in term of photonic efficiency and selectivity of CO2 reduction is of demand interest for future work. © The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2025.